Selenium Transfer between Kaolinite or Goethite Surfaces, Nutrient Solution and Oryza Sativa - Nothstein, Alexandra Kelly (Karlsruher mineralogische und geochemische Hefte : Schriftenreihe des Instituts für Angewandte Geowissenschaften, 2016)
The aim of this study was to describe and quantify Se transfer at the interface between soil and plant. For this purpose, three Se reservoirs were defined: soil, soil solution and plant, represented by kaolinite or goethite, nutrient solution and rice. First, Se transfer from solution to plant and Se partitioning in the plant was studied; then adsorption-desorption processes of Se onto kaolinite and goethite were investigated. Finally, a mass balance of the combined experiment was modelled.